Electronic word of mouth, brand image, and service quality as predictors of purchase decisions at Kimino Coffee and Eatery, Pulau Rakyat, Asahan - Risfika Indah Lestari; Neni Triastuti (Privietlab, 2026)
The rapid expansion of the Indonesian coffee-shop industry has transformed the local café from a place of consumption into a contested marketplace in which consumer-generated information, symbolic brand meaning, and experiential service all compete to shape the buying decision. This study examines the simultaneous and partial effects of electronic word of mouth (e-WOM), brand image, and service quality on purchase decisions at Kimino Coffee and Eatery in Pulau Rakyat, Kabupaten Asahan, Indonesia. A quantitative associative survey design was adopted. Primary data were collected through a five-point Likert questionnaire administered to 96 consumers selected by non-probability purposive sampling, with the sample size determined using the Cochran formula for an unknown population. The respondent profile comprised 63 women (65.6%) and 33 men (34.4%). Data were analysed using multiple linear regression after validity, reliability, and classical-assumption testing. The three predictors jointly explained 75.0% of the variance in purchase decision, F(3, 92) = 91.852, p < .001. Partially, e-WOM exerted a positive and significant effect (β = .379, p < .001), and brand image emerged as the dominant predictor (β = .497, p < .001), whereas service quality was positive but statistically non-significant (β = .040, p = .690). The results indicate that in a competitive café context, social proof and symbolic brand identity drive the decision to buy, while a baseline level of service quality functions as a hygiene factor that no longer differentiates among local establishments. Theoretical and managerial implications for café marketing are discussed.